Absorption and translocation of polybrominated diphenyl ethers (PBDEs) by plants from contaminated sewage sludge - Vrkoslavová, Jana; Demnerová, Katerina; Macková, Martina; Zemanová, Tereza; Macek, Tomás; Hajslová, Jana; Pulkrabová, Jana; Hrádková, Petra; Stiborová, Hana (Chemosphere, 2010)
Polybrominated diphenyl ethers (PBDEs) are used as additive flame retardants. PBDEs are persistent, bioaccumulative and toxic compounds. They are often detected in sewage sludge which is applied on agricultural soils as fertilizer. The objective of this study was to find out whether plants are able to accumulate and translocate PBDEs. Tobacco (Nicotiana tabacum) and nightshade (Solanum nigrum) were planted in pots containing contaminated sewage sludge and uncontaminated substrate. After 6 months of plant cultivation in sewage sludge up to 15.4 ng g(-1) dw and 76.6 ng g(-1) dw of PBDE congeners--BDE 47, BDE 99 and BDE 100---were accumulated in the nightshade and tobacco tissue, respectively. Corresponding values in plants vegetated in the control garden substrate were 10 times lower. The bioconcentration factors (BCFs) of accumulated congeners were calculated. Tobacco exhibited higher BCFs values and for both plants BCFs values of BDE 47, BDE 99, BDE 100 and BDE 209 negatively correlated with their octanol-water partition coefficients (logK(ow)). The exception was decaBDE (BDE 209) which was accumulated only in tobacco tissue in the concentration of 116.8 ng g(-1) dw. The majority of PBDEs was detected in above-ground plant biomass indicating that both plants have the ability to translocate PBDEs. To our knowledge this is one of the first studies reporting the accumulation of both lower PBDEs and BDE 209 in plants. Our results suggest that absorption, accumulation and translocation of PBDEs by plants and their transfer to the food chain could represent another possible risk for human exposure.
Keywords: Sewage; odpadní vody; vývoj rostlin; biodegradace; Halogenated Diphenyl Ethers; Plants; Biodegradation, Environmental; Nicotiana; retardanty hoření; tabák; látky znečišťující půdu; rostliny; Soil Pollutants; Solanum; halogenované difenylethery; Plant Development; Flame Retardants